WRITING IN ENGLISH FOR INTERNATIONAL CONFERENCES - Phillip Sanger; Yulia N. Ziyatdinova (Высшее образование в России)
This article is the result of a two-hour workshop given to new faculty attending the International Scientific School on Engineering Education for New Industrialization held in Kazan, Tatarstan from September 23–28, 2013. The goal of the workshop was to help faculty who are interested in publishing in English at conferences. The workshop had three parts: selecting the best venue, creating an interesting title and writing a good abstract.